A rapidly-exploring random tree-based intelligent congestion control through an alternate routing for WSNs. (9th November 2022) - Prakash, P. Suman; Kavitha, D.; Reddy, P. Chenna
In wireless sensor networks (WSNs), congestion is a challenging issue, and it degrades the efficiency in terms of packet loss, energy wastage, throughput, etc. The primary cause of the congestion in WSNs is the data routing of the many-to-one pattern. It means multiple nodes can send their data to a single sink using multi-hop transmissions. To control the congestion in WSN, we use a rapidly-exploring random tree (RRT)-based mechanism to divert the data packets from the congested nodes. Initially, we use a mathematical model to determine the congested nodes in the WSNs. Further, we identify the routing path using the RRT algorithm in which the algorithm can construct a dynamic routing while avoiding the congested nodes in the routing path. We estimate the efficiency of our approach using simulation runs and compare the results using the recently published algorithm. We notice the improved performance in our method.